It's been years since I've done maths properly so I'm rusty with it. I'm helping out a colleague at work who is studying maths for an OU course. 1. The problem statement, all variables and given/known data Part 1: Differentiate function. f(x) = e^(0.5x+cos(x)) Part 2: Use answer from part 1 to show. g(x) = (1+2sinx)(e^(0.5x+cos(x))) Has the derivative: g'(x) = 0.5(4cos^2(x)+4cos(x)-3)(e^(0.5x+cos(x))) 3. The attempt at a solution A=e^(0.5x+cos(x)) Part 1: Using chain rule f'(x) = A(0.5-sin(x)) Part 2: Using this and the product rule I get. g'(x) = 0.5A(4cos(x)-4sin^2(x)+1) Which isn't the same.